UJI BEBERAPA DOSIS MINYAK SERAI WANGI (Cymbopogon nardus L.) SEBAGAI ATRAKTAN HAMA LALAT BUAH (Bactrocera sp) PADA TANAMAN JERUK SIAM (Citrus nobilis Lour.) - Hafiz Fauzana; Aurilika Octiyanti (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2021)
Siamese orange (Citrus nobilis Lour) is a horticultural plant having the main pest, the fruit flyBactrocera sp. The solution is eviromentally friendly control is the use of trap combined with theattractant of lemongrass (Cymbopogon nardus L.). The purpose of this study is to get the dosage oflemongrass oil which is ablest to trap most fruit fly on citrus plants. This research was conducted atDesa Kuok Kecamatan Kuok Kabupaten Kampar and at Riau University Faculty of AgricultureLaboratory of Plant Pests, from September to November in 2020. The treatment of the givendosage of lemongrass oil was 0,125 ml per trap, 0,250 ml per trap, 0,375 ml per trap, 0,500 ml pertrap, and 0,625 ml per trap. The experiment used a complete randomized design with 5 treatmentsand 4 repetitions. The result showed that the species that attacks the citrus plant is B. carambolae,B. papaye dan B. umbrosa. The ablest dosage of lemongrass oil in trapping most fruit fly was 0,625ml trap with an average population of 18,5 fruit flies for seven days.